3D virtual barrier lake platform building method of based on multi-source sensing data. Issue 3 (May 2021) - Sun, Liming; Wei, Yingqi; Yan, Jun
Abstract: The huge flood disaster caused by the barrier lake in a short time usually requires precise emergency decision-making, and the 3D virtual platform of the barrier lake is one of the most important informational support. Traditionally, there are few studies on the reconstruction technology of scale 3D dam lake model based on multi-source perception data. This paper summarizes the types of multi-source perception data used for 3D modeling of barrier lake, and proposes a method for designing and defining 3D data models of barrier lake, a large-scale and a fine local-scale 3D model reconstruction method are studied, building methods are summarized for the main steps of 3D dynamic event simulation, and finally this gives the software architecture design of the barrier lake 3D model platform, Baige barrier lake is taken as an example for practical development and verified the rationality of the method and Feasibility, the software platform provides an important basis for the rescue and disaster relief of the barrier lake in the future.